(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
The study was intended to observe the diversity and the distribution of mangrove plants species on southern and northern coast of Central Java Province. This research was conducted in July till December 2003, at 20 sites. Laboratory assay was conducted in Laboratory of Biology Department, Faculty of Mathematics and Natural Sciences, and Central Laboratory of Mathematics and Natural Sciences, Sebelas Maret University (UNS) Surakarta. Plant specimens were collected by using survey method, than it was identified and preserved as herbaria. The result indicated that there was 55 species (27 families) of mangrove plants in Central Java, composed by major (17), minor (12), and association (26) plants, with habits i.e. trees (32), bushes (13), and herbs (10). The species of major mangrove plant with the broadest range of site distribution were R. mucronata (16), followed by S. alba (15), N. fruticans (12), A. alba and A. marina (each was 11). The species of minor mangrove plant with the broadest range of site distribution was A. aureum (11). The associative plant of mangrove with the broadest range of site distribution was A. ilicifolius (16), D. trifoliata (15), C. gigantea (13), H. tiliaceus (11), T. catappa (11), and I. pes-caprae (10). The other species were distributed in less than 10 sites. The location with the most varied species diversity was Wulan (35), the next was Motean and Muara Dua (each was 29), Bogowonto (19), Pasar Banggi (18), Tritih (17), Sigrogol (15), Juwana and Ijo (each was 14), Cakrayasan (12), Lasem and Serang (each was 11), Bulak, Telukawur, Cingcingguling and Bengawan (each was 9), Pecangakan (8), Serang (6), and the last was Tayu (5). Â© 2005 Jurusan Biologi FMIPA UNS Surakarta Key words: mangrove plants, species diversity, Central Java Province.